Identification of Diverse Bacteriophages Associated with Bees and Hoverflies - Rohan A. Bandoo; Simona Kraberger; Cahit Ozturk; Michael C. Lund; Qiyun Zhu; Chelsea Cook; Brian Smith; Arvind Varsani (Viruses)
Bacteriophages are the most numerous, ubiquitous, and diverse biological entities on the planet. Prior studies have identified bacteriophages associated with pathogenic and commensal microbiota of honeybees. In this study we expand on what is known about bacteriophages from the lineages Caudoviricetes, Inoviridae, and Microviridae, which are associated with honeybees (Apidae, Apis mellifera), solitary bees of the genus Nomia (Halictidae, Nomia), and hoverflies (Syrphidae). The complete genomes of seven caudoviruses, seven inoviruses, and 288 microviruses were assembled from honeybees (n = 286) and hoverflies in Arizona (n = 2). We used bacterial host predictive software and sequence read mapping programs to infer the commensal and transient bacterial hosts of pollinating insects. Lastly, this study explores the phylogenetic relationships of microviruses sampled from bees, opportunistically sampled pollinating insects such as hoverflies, and blackflies.